PENGARUH KEDALAMAN TANAM YANG BERBEDA TERHADAP PERTUMBUHAN DAN KUALITAS AGAR RENDEMEN RUMPUT LAUT(Gracilaria gigas)DENGANMETODE LEPAS DASAR - Gani Yusril Fikri; Andi Rahmad Rahim; Farikhah Farikhah (Jurnal Perikanan Pantura (JPP), 2018)
Gresik Regency is faced with the problem of development which is less attention to spatial arrangement where the pond land is threatened by land conversion for settlement, urban development, and industry. As one of the Minapolitan areas in Indonesia, the profile of pond farming in Gresik Regency needs attention. The purpose of this research is to analyze the growth of Gracilaria gigas seaweed in ponds with different depth of cultivation and to analyze the quality in order to rendemen Gracilaria gigas seaweed in ponds with different depth of cultivation, which is cultivated by the off bottom method. The study was conducted in February 2018 with a study duration of 42 days. The test plants used in this study were seaweed of Gracilaria gigas species, which were cultivated by the off bottom method. The experimental design used was complete randomized design (RAL) with 4 different planting depth treatment and 3 replications ie treatment A (depth 20 cm), B (depth 40 cm), C (depth 60 cm) and D (depth 0 cm).